KEBERPIHAKAN NEGARA TERHADAP UPAYA PENGENTASAN KEMISKINAN DI PEDESAAN - Tutik Nurul Jannah (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IPMAFA, 2017)
Desa is the region where the cultural base of Indonesian society. Desa has an important role in an attempt to resolve the problem of poverty. Government spending allocated for development of desa as mandated by the Act No.6 / 2014 should be viewed in the perspective of the state alignments against efforts to resolve the problem of poverty. The state alignments in solving various problems concerning the interests of the Indonesian people can actually be seen from the regulations drawn up and enforced. The state alignments in resolving disputes in pedesaan can be explored through the juridical studies in the Act No. 6/2014 by using analysis from the political perspective of the law.